[OA013] Treatment accuracy in surface guided deep-inspiration breath-hold radiotherapy for left-sided breast cancer. (August 2018) - Worm, Esben; Offersen, Birgitte; Poulsen, Per R.; Askholm, Ellen; Yates, Esben S; Hansen, Rune
Abstract : Purpose: To evaluate the setup accuracy and intrafraction stability in deep-inspiration breath-hold (DIBH) surface guided radiotherapy (SGRT) for left-sided breast cancer. Methods: Five patients received 15 ( n = 4) or 18 ( n = 1) fractions of radiotherapy for left-sided breast cancer. Treatment planning was based on two opposing fields, aligned tangentially to the thoracic wall. At treatment, patient setup was initially guided by an optical SGRT system such that the breast surface during DIBH corresponded (within ±3 mm and ±3 degrees) to the projected breast surface of the DIBH planning-CT. The couch was then repositioned during DIBH according to daily orthogonal MV (matching thoracic wall) and kV (matching ribs, junction of the clavicle and sternum) image-guidance and a new reference position of the breast surface was recorded by the SGRT system. The treatment was delivered with a ±3 mm and ±3 degrees DIBH gating window around this reference position as guided by the SGRT system. The PTV margins required for SGRT setup without MV/kV image guidance were calculated from the errors in the MV/kV setup images (van Herk recipe, Semin Radiat Oncol, 2004). The intrafraction error of the thoracic wall was assessed from an MV image acquired during delivery of each treatment field, i.e. near the beginning and end of each treatment fraction. Results: The mean ( ± SD) 3D SGRT setup error was 0.49 ± 0.26 cm. Without image-guidance, the PTV margins required to account for SGRT setup errors would have been 0.68 cm (AP), 0.49 cm (CC) and 0.90 cm (LR). The mean absolute intrafraction error in the direction orthogonal to the thoracic wall was 0.10 ± 0.09 cm and 0.16 ± 0.13 cm during the first and second treatment field, respectively. The difference in mean error was significant (p < 0.001, paired t-test). For one of the five patients, the heart unintendedly extended 0.6–0.9 cm into the treatment fields in 5 out of 15 fractions. Conclusions: Due to changes in breast size and shape, SGRT should be supplemented by daily image-guidance for optimal setup accuracy. SGRT ensured a high intrafraction stability of the thoracic wall with a slight decline in accuracy near the end of treatment. At the time of writing, more patients are being included in the study.